2006
DOI: 10.1002/jnr.21043
|View full text |Cite
|
Sign up to set email alerts
|

Novel roles for metallothionein‐I + II (MT‐I + II) in defense responses, neurogenesis, and tissue restoration after traumatic brain injury: Insights from global gene expression profiling in wild‐type and MT‐I + II knockout mice

Abstract: Traumatic injury to the brain is one of the leading causes of injury-related death or disability, especially among young people. Inflammatory processes and oxidative stress likely underlie much of the damage elicited by injury, but the full repertoire of responses involved is not well known. A genomic approach, such as the use of microarrays, provides much insight in this regard, especially if combined with the use of gene-targeted animals. We report here the results of one of these studies comparing wild-type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 168 publications
4
34
0
Order By: Relevance
“…Therefore, cryolesion is a model that elicits an inflammatory response at the gene level, in agreement with previous results Penkowa et al, 2006). The effect of cryolesion at a transcriptome level has been already described by our group in animals lacking IL-6 (Poulsen et al, 2005), metallothioneins 1 and 2 (Penkowa et al, 2006), and TNFareceptor 1 or receptor 2 (Quintana et al, 2007).…”
Section: Gene Selection and Functional Analysissupporting
confidence: 85%
See 2 more Smart Citations
“…Therefore, cryolesion is a model that elicits an inflammatory response at the gene level, in agreement with previous results Penkowa et al, 2006). The effect of cryolesion at a transcriptome level has been already described by our group in animals lacking IL-6 (Poulsen et al, 2005), metallothioneins 1 and 2 (Penkowa et al, 2006), and TNFareceptor 1 or receptor 2 (Quintana et al, 2007).…”
Section: Gene Selection and Functional Analysissupporting
confidence: 85%
“…As previously described in cryolesion (Poulsen et al, 2005;Penkowa et al, 2006;Quintana et al, 2007), a clear pattern of induction was observed, with genes up-regulated by the cryolesion at 1 day post lesion (dpl) (Fig. 4), both at 1-4 dpl (Fig.…”
Section: Gene Selection and Functional Analysismentioning
confidence: 50%
See 1 more Smart Citation
“…As expected [35][36][37] , a clear pattern of responses was observed, with genes being either up-or downregulated by the cryolesion readily identified by the hierarchical clustering analyses. Genes upregulated at 1 day after lesion constituted the largest cluster in our study, comprising 141 genes of a total of 174.…”
Section: Gene Selectionmentioning
confidence: 68%
“…Gene knockouts in the laboratory mouse have produced particularly successful research, and efforts are being made to knockout each mouse gene for worldwide availability [34] . We have already shown results obtained in IL-6 knockout [35] , TNFR1 or TNFR2 knockout [36] and MtI&II knockout mice [37] that fully illustrate these points. A complementary approach is to analyze transgenic mice with overexpression of a given gene.…”
Section: Introductionmentioning
confidence: 65%